A New Risk-Scoring System for Colorectal Cancer and Polyp Screening by Turkish Colorectal Cancer and Polyp Study Group - Erdem, Levent; Akbal, Erdem; Koçak, Erdem; Tucer, Dilek; Üçbilek, Enver; Uyanıkoğlu, Ahmet; Dolapçıoğlu, Can; Ahısalı Erim, Emel; Şirin, Göktuğ; Alkım, Hüseyin; Soylu, Aliye; Doğanay, Levent; et al. (Turkish Journal of Gastroenterology, 2022)
Background: Colorectal cancer is one of the most commonly diagnosed types of cancer worldwide. An early diagnosis and detection of colon cancer and polyp can reduce mortality and morbidity from colorectal cancer. Even though there are a variety of options in screen- ing tests, the question remains on which test is the most effective for the early detection of colorectal cancer. In this prospective study, we aimed to develop a simple, useful, effective, and reliable scoring system to detect colon polyp and colorectal cancer.Methods: We enrolled 6508 subjects over the age of 18 from 16 centers, with colonoscopy screening. The age, smoking status, alcohol consumption, body mass index, polyp incidence, polyp size, number and localization, and pathologic findings were recorded.Results: The age, male gender, obesity, smoking, and family history were found as independent risk factors for adenomatous polyp. We have developed a new scoring system which can be used for these factors. With a score of 4 or above, we found the following: sensitivity 81%, specificity 40%, positive predictive value 25.68%, and negative predictive value 89.84%, for adenomatous polyp detection; and sensitivity 96%, specificity 39%, positive predictive value 3.35%, negative predictive value 99.29%, for colorectal cancer detection. Conclusion: Even though the first colorectal cancer screening worldwide is generally performed for individuals over 50 years of age, we recommend that screening for colorectal cancer might begin for those under 50 years of age as well. Individuals with a score ≥ 4 must be included in the screening tests for colorectal cancer.